Narrative Relations and Associations: Catherine Kohler Riessman’s Research Dialogism - Esin, Cigdem; Squire, Corinne (Narrative Works, 2020)
In this paper, Esin and Squire provide their individual and collective reflections on the influence of Catherine Kohler Riessman’s dialogical approach in research. Each researcher reinterpreted the dialogism in Riessman’s approach in their own work, focusing on differing elements of it. While Esin examines her experience of relationality, reflexivity, and positionality in her work, Squire discusses her adoption of the approach to develop methodological interdisciplinarity in social science research. The authors then reflect on their dialogue in researching multimodal narratives, historical positioning in and beyond narratives, and power relations in the context of research.